Cross-Cultural adaptation and validation of the Exercise-Induced Leg Pain questionnaire for Spanish speaking patients. - Castillo-Domínguez, Alejandro; Alvero-Cruz, José Ramón; Páez-Moguer, Joaquín; Nauck, Tanja; Lohrer, Heinz; Scheer, Volker; García-Romero, Jerónimo (SAGE, 2022)
The objectives of this study were to cross-culturally adapt a Spanish version of the original German Exercise-Induced Leg Pain (EILP-G) questionnaire for the determination of symptom severity, function, and sport capacity in patients with EILP and to determine the psychometric properties of the version developed in Spanish (EILP-Sp). The EILP-G questionnaire was cross-culturally adapted to Spanish according to the established guidelines. The validity and reliability of the EILP-Sp were assessed in four groups of participants (n = 160) by analyzing six psychometric properties. Excellent internal consistency (Cronbach’s α = 0.942) and test-retest reliability (Rxx = 0.998) were found. The results of the exploratory and confirmatory factor analyses indicated that EILP was the only construct measured from the EILP-Sp. The correlation between the EILP-Sp total score and the dimensions of the SF-36 questionnaire showed good construct validity, with 80% of the previously stated hypotheses being met. Concurrent validity, assessed by the Schepsis scale, was almost perfect (r = 0.92, p<.001). Predictive validity was tested using the ROC curve, indicating the ability of the EILP-Sp questionnaire to discriminate between injured and healthy subjects (area of .992; 95% CI: .983–1, p<.001). As no individuals with EILP obtained the maximum or minimum possible values on the questionnaire, there were no ceiling or floor effects. The Spanish version was successfully adapted from the original EILP-G, resulting in a reliable and valid patient-reported outcome measure for the assessment of patients with chronic EILP.
Keywords: Dolor; Piernas; Carrera; exercise-induced leg pain; patient-reported outcomes measures; psychometrics; reliability; validity; running